LEVERAGE, LIKUIDITAS, DAN PERTUMBUHAN ASET SEBAGAI FAKTOR PENENTU PROFITABILITAS PERUSAHAAN - Kamil, Bilqis Ratulia; Kinasih, Hayu Wikan (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to identify the effect of leverage, liquidity, and asset growth on profitability. This study focuses on consumer cyclicals and non-cyclicals sector companies listed on the Indonesia Stock Exchange in 2020-2023. In this study, leverage is calculated using the Debt to Equity Ratio, liquidity is calculated using the Current Ratio, and asset growth is calculated using Growth Asset. While profitability is proxied using Return of Equity. The type of data used is quantitative data obtained from secondary sources, namely in the form of annual reports. This study uses a purposive sampling method, with 63 data as the number of samples. Data analysis techniques applied in this study is multiple linier regression analysis. The results of this study state that leverage (DER) has a significant positive effect on profitability (ROE), liquidity (CR) has a significant positive effect on profitability (ROE), and asset growth (GA) has a significant positive effect on profitability (ROE). Keywords: leverage; liquidity; asset growth; profitability.